PROGRESS ON YTTRIA-STABILIZED ZIRCONIA SENSORS FOR HYDROTHERMAL PH MEASUREMENTS - Lvov S.N.; Zhou X.Y.; Ulmer G.C.; Barnes H.L.; Macdonald D.D.; Ulyanov S.M.; Benning L.G.; Grandstaff D.E.; Manna M.; Vicenzi E. (My University, 2003)
Electrochemical cells are reviewed and a new design is evaluated for potentiometric pH measurements to above 300 °C. The new design system minimizes the effects of metal corrosion on measured pH. In addition, a recently developed [Zhou, X.Y., Lvov, S.N., Ulyanov, S.M., 2003. Yttria-Stabilized Zirconia Membrane Electrode, US Patent #6, S17, 694] flow-through, yttria-stabilized zirconia (YSZ) pH sensor has been further tested. The Nernstian behavior and precision of the YSZ electrode were evaluated by measuring the potentials vs. H2-Pt electrode at 320 and 350 °C. Also, using the YSZ electrode, the association constants of HCl(aq) at 320 and 350 °C have been determined from the potentials of a HCl(aq) solutions at 0.01 to 0.001 mol kg-1. The results, pK320=-1.46+/-0.46 and pK350=-2.35+/-0.25, in good agreement with literature data, both demonstrate the effective use of the cell and YSZ electrode for pH measurements to about +/-0.05 pH units, and confirm the Nernstian behavior of the YSZ electrode in acidic HCl solutions up to 350 °C. Commercial YSZ tubes available for high-temperature pH sensing are, however, far from ideal because of irregular compositions, phase structures, and interstitial materials. A consequence is the premature structural decay of YSZ tubes in acidic solutions at elevated temperatures. In spite of the long-term decay, YSZ sensors respond rapidly to changes in pH, apparently limited only by the rate of mixing of solutions within the cell. This system makes the measurement feasible above 300 °C of mineral hydrolysis equilibrium constants and their free energy changes within uncertainties of about +/-1.0 kJ.
Keywords: HIGH TEMPERATURE; ELECTROCHEMICAL CELLS; HYDROTHERMAL SOLUTIONS; YTTRIA-STABILIZED ZIRCONIA PH SENSOR; ASSOCIATION CONSTANTS OF HCL(AQ)